Retrospective evaluation of recurrent secondary septic peritonitis in dogs (2000–2011): 41 cases. Issue 2 (2nd November 2015) - Barfield, Dominic M.; Tivers, Michael S.; Holahan, Matthew; Welch, Kristin; House, Arthur; Adamantos, Sophie E.
Abstract: Objective: To describe the clinical characteristics of recurrent septic peritonitis in dogs. Design: Multicenter retrospective observational study. Animals: Client‐owned dogs with recurrent septic peritonitis. Setting: Three university emergency and referral hospitals. Interventions: None. Measurements and Main Results: Medical records from 3 veterinary university teaching hospitals were reviewed and data were collected using a standardized data collection sheet for all cases of septic peritonitis during the study period (2000–2011). Forty one dogs met the inclusion criteria for recurrent peritonitis. All dogs underwent relaparotomy. The original cause of septic peritonitis in these cases included previous surgery for gastrointestinal foreign body removal ( n = 26), gastrointestinal neoplasia ( n = 3), gastric or duodenal ulceration ( n = 3), bilary tract leakage ( n = 2), and single instance for each of the following: penetrating foreign body, hernia strangulation, intussusception, mesenteric volvulus, infection of the laparotomy incision, prostatic abscess, and trauma. Eighteen animals survived to discharge. There was no difference detected between survivors and nonsurvivors with recurrent peritonitis in terms of inciting cause, serum albumin concentration, surgical management, or provision of appropriate initial antimicrobials. The survival rate for dogs having recurrent peritonitis was 43.9% (18/41 dogs). Conclusions: This retrospective study did not identify any significant prognostic indicators for dogs with recurrent peritonitis and that the mortality rate for dogs having more than one surgery for septic peritonitis is similar to that reported for a single surgery for septic peritonitis.